REE and elemental contents and isotopic compositions in foraminifera from DSDP Hole 39-357 - Martin R Palmer; Henry Elderfield (PANGAEA, 1986)
An evaluation has been made of the method of establishing the REE contents and patterns and Nd isotopic compositions of sea water over Cenozoic time from their record in the FeMn-oxide coatings of foraminiferal calcite. Using 0-60 Ma samples from the Rio Grande Rise (DSDP Site 357) it has been established that the REE contents of the coatings are generally similar to those of Recent samples. However, in the Cenozoic samples the surface coatings have been diagenetically modified under suboxic conditions resulting in a distinctly different REE pattern although the original 143Nd/144Nd ratios appear to have been preserved. The Nd isotopic curve for Cenozoic sea water in the S. Atlantic shows clear temporal trends, although these are not so extreme as to show 143Nd/144Nd ratios outside the range observed in modem sea water. With the principal exception of the oldest samples there is an approximate inverse relationship between the Nd and Sr isotopic compositions of the foraminifera. It is suggested that the changes reflect both global changes in the relative proportions of Nd and Sr derived from continental input and from the weathering of volcanic debris together with short term and local variations to which the Sr curve is insensitive, reflecting the different response times of the two elements to changes in oceanic input functions. The Nd isotope curve appears to be a potentially useful tracer of ocean palaeochemistry.
Supplement to: Palmer, MR; Elderfield, H (1986): Rare earth elements and neodymium isotopes in ferromanganese oxide coatings of Cenozoic foraminifera from the Atlantic Ocean. Geochimica et Cosmochimica Acta, 50(3), 409-417, https://doi.org/10.1016/0016-7037(86)90194-8